PENGARUH MANAJEMEN PERKANTORAN TERHADAP EFEKTIFITAS KERJA PADA SMP 35 SENDAWAR LINGGANG MELAPEH KABUPATEN KUTAI BARAT - Mardita, Kornelia (PREDIKSI, 2014)
ABSTRACT This research aims to 1) To find answers to problems which writer open previously 2) To prove the truth of research hypothesis which have been formulated.Research executed in environment work the SMP Negeri 35 Kabof Regency Kabupaten Kutai Barat cy Melak Sampel taken in census, that is as much 35 responder. Data collecting do by Library Research, Field of Work Research, Interview the, Quesioner, and Document. Data Analyse with the Correlation of Doubled Linear Product Moment and Rgresi. Hypothesis Examination use the Uji-T and Uji-F level 5%.Research result conclude that 1) White colars Management will only influence the Efektifitas Work equal to 22,50%; while rest [of] equal to 77,50% influenced by other variable, besides white colars management variable consisted by the planning, organization, and operation 2) The Simultan there are influence which white colars signifikan management to effectivity work in SMP Negeri 35 Sendawar Kabupaten Kutai Barat 3) By parsial there are influence which signifikan of planning and organization to work effectivity in SMP 35 Sendawar Kabupaten Kutai Barat But operation donot give the influence which signifikan to efekifitas work.